Paula Bruno, Martín García Mérou. Vida intelectual y diplomática en las Américas. Bernal, Universidad Nacional de Quilmes, 2018 - Fontana, Patricio (Badebec, 2019)
Paula Bruno, Martín García Mérou. Vida intelectual y diplomática en las Américas. Bernal, Universidad Nacional de Quilmes, 2018